Distributed Spectrum Coordination using Decoupled Permissioned Blockchains - Veloso, Alan; Sousa, Jeffson; Saraiva, Filipe; Abelém, Antônio (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF); 2026: Anais do XVII Workshop de Pesquisa Experimental da Internet do FuturoDO - 10.5753/wpeif.2026.23293, 2026)
While decentralized Dynamic Spectrum Access (DSA) improves multi-operator coordination, existing blockchain solutions are slow because they tightly couple consensus mechanisms with time-sensitive radio operations. To overcome this bottleneck, we propose a hybrid architecture that logically decouples these planes, ensuring that only normatively relevant state transitions (e.g., spectrum grants) require synchronous blockchain validation. Informational requests and routine heartbeats are processed entirely off-chain to minimize latency. By using a permissioned blockchain and smart contracts selectively, our system maintains a secure and consistent World State without stalling continuous radio operations. Experimental evaluations demonstrate that confining distributed consensus (averaging 1.8s latency) to critical operations successfully replaces implicit trust with algorithmic guarantees, remaining fully compatible with CBRS/SAS latency budgets.